Recollections of the 6th Music Therapy World Congress from the Chair of the Scientific Committee - Barcellos, Lia Rejane Mendes (Voices: A World Forum for Music Therapy, 2010)
As 1990 began, the new President of Brazil assumed his position confiscating the money of every Brazilian who had saved his/her money. It was in this difficult political, economic and emotional context, without any money, that the VI World Congress held in Rio de Janeiro was organized, under the leadership of Professor Cecilia Conde, the president of the meeting.